Synthesis and structural Behaviour of Schiff Base Complexes Derived from Vanillin and Aliphatic Diamines - Kumar, Mithilesh; Prasad, R.J.; Bhattacharya, Supriti (Asian Journal of Chemistry, 2010)
Schiff base complexes derived from ligands vanillin and aliphatic diamines (1,4-diaminobutane and 1,6-diaminohexane) with divalent Co2+, Ni2+ and Cu2+ ions have been synthesised. Square planar geometry has been assigned to [M(L1)2]SO4 and [M(L2)2)SO4, where M = Cu2+, L1 = Schiff base ligand derived from vanillin and 1,4-diaminobutane(PMBIB) and L2 = Schiff base ligand derived from vanillin and 1,6-diaminohexane (PMBIH); whereas octahedral structures have been assigned to [M(L1)2(NO3)2], [M(L2)2(NO3)2] and [M(L1)2(CH3COO)2] complexes (M = Cu2+, Co2+, and Ni2+).